Anti-Diabetic Effect of Ethanolic and Methanolic Leaves Extract of Centella Asiatica on Alloxan Induced Diabetic Rats - P.K.CHAUHAN; I.P.PANDEY; VINOD KUMAR DHATWALIA; V.SINGH (International Journal of Pharma and Bio Sciences, 2010)
The Ethanolic and Methanolic extracts of the leaves of Centella asiatica (Family- Umbelliferare) were tested for anti-diabetic activity, by glucose tolerance test in normal rats and alloxan induced diabetic rats. Ethanolic and methanolic extracts had shown significant protection and lowered the blood glucose levels to normal in glucose tolerance test. In alloxan induced diabetic rats the maximum reduction in blood glucose was observed after 3h at a dose level of 250 mg/kg of body weight. The percentage protections by ethanolic and methanolic extracts were 48% and 30% respectively. In long term treatment of alloxan induced diabetic rats, the degree of protection was determined by measuring blood glucose, triglycerides, cholesterol and urea levels on 0,3,5,7 and 10th day. Both the extracts showed a significant anti- diabetic activity comparable with that of glibenclamide. The histopathological studies during the long-term treatment have shown to ameliorate the biochemical damages caused by alloxan. These results indicate that the Centella asiatica leaves possess significant anti – diabetic activity.